Predicting Tourists’ Behaviour Towards Smart Tourism: The Case in Emerging Smart Destinations - Novianti, Syifaa; Susanto, Eko; Rafdinal, Wahyu (Journal of Tourism Sustainability, 2022)
This paper aims to investigate the tourist behaviour towards smart tourism in the case of emerging smart destinations. The extended model of theory of planned behaviour (TPB) is proposed as a tool to predict the relationship between applying smart tourism technology and tourist behaviour in selecting and visiting the destination. Using the city of Bandung, Indonesia as a case study, data was collected using a structured questionnaire from 524 domestic tourists in several emerging smart destinations. The confirmatory factor analysis was utilised to test the construct validity and reliability of the model, while Partial Least Squares (PLS) modelling was employed to assess the hypotheses developed. The results show that the extended TPB model can reasonably predict the tourist behaviour towards smart tourism, suggesting its applicability to emerging smart destinations. Smart tourism technology directly affects tourists’ attitude, subjective norms, and tourists perceived behavioural control, resulting in their travel intention. Also, their planned behaviour mediates the relationship between smart tourism technology and tourist decision in selecting and visiting destinations. Identifying predictors of tourist behaviour towards smart tourism provides a more accurate forecast of tourist demand, thereby enabling policymakers to tailor and implement a more comprehensive smart tourism planning and development